The Impact of Breastfeeding Technique Education on the Effectiveness of Postpartum Mothers in Breastfeeding at Montong Betok Health Center - Fatmasari, Baiq Dika; Ernawati, Ernawati; Wirastri, Dwi (Ahmar Metastasis Health Journal, 2024)
Exclusive breastfeeding involves providing only breast milk without any additional liquids or solid foods, except for vitamins, minerals, or medications in drop or syrup form, until the baby is six months old. The correct breastfeeding technique can enhance the success of exclusive breastfeeding. This study aims to determine the impact of breastfeeding technique education on the effectiveness of postpartum mothers in breastfeeding at Montong Betok Health Center. The research method employed is quantitative with a pre-experimental design using a one-group pretest and posttest approach. The population includes all mothers who gave birth at Montong Betok Health Center from November 1 to December 31, 2022, totaling 30 individuals. The sampling technique used is total sampling, encompassing 30 participants. Data collection was conducted through observation sheets. The data were analyzed using the Wilcoxon test. The results indicated that the effectiveness of breastfeeding techniques before education was in the sufficient category for 29 participants (96.7%), and after education, it improved to the good category for 20 participants (66.7%). There is a significant impact of breastfeeding technique education on the effectiveness of postpartum mothers in breastfeeding at Montong Betok Health Center, with a p-value of 0.000 < 0.05. This means that breastfeeding technique education positively affects the effectiveness of postpartum mothers in breastfeeding at Montong Betok Health Center.